Antitumor Effects of Cannabinoids in Human Pancreatic Ductal Adenocarcinoma Cell Line (Capan-2)-Derived Xenograft Mouse Model - Sakarin, Siriwan; Meesiripan, Nuntana; Sangrajrang, Suleeporn; Suwanpidokkul, Nuntakan; Prayakprom, Piyaporn; Bodhibukkana, Chatchada; Khaowroongrueng, Vipada; Suriyachan, Kankanit; Thanasittichai, Somchai; Srisubat, Attasit; Surawongsin, Pattamaporn; Rattanapinyopituk, Kasem (Frontiers in Veterinary Science, 2022)
Background: Pancreatic cancer is considered as a rare type of cancer, but the mortality rate is high. Cannabinoids extracted from Cannabis plant has been interested as an alternative treatment in cancer patients. Only few literatures are available on antitumor effects of cannabinoids in pancreatic cancer. Therefore, this study aims to evaluate the antitumor effects of cannabinoids in pancreatic cancer xenografted mouse model. Materials and Methods: Twenty-five nude mice were subcutaneously transplanted with human pancreatic ductal adenocarcinoma cell line (Capan-2). All mice were randomly assigned into 5 groups including negative control (gavage with sesame oil), positive control (5 mg/kg 5-FU intraperitoneal administration), cannabinoids groups that daily received THC:CBD, 1:6 at 1, 5 or 10 mg/kg BW for 30 days, respectively. Xenograft tumors and internal organs were collected for histopathological examination and immunohistochemistry. Results: The average tumor volume was increased in all groups with no significant different. The average apoptotic cells as well as caspase-3 positive cells were significantly increased in cannabinoids groups compared with negative control group. The expression score of PCNA in positive control and cannabinoids groups were decreased compared with negative control group. Conclusions: Cannabinoids have an antitumor effect on Capan-2 derived xenograft mouse model though induce apoptosis and inhibit proliferation of tumor cells in the dose dependent manner.